The effect of fertilizers on the biochemical composition of Oxycoccus macrocarpus Ait. Pers. fruits on cutover peatlands in the central and northern agroclimatic zones of the Republic - Rupasova, Zhanna A.; Vasilevskaya, Tamara I.; Krinitskaya, Natalia B.; Zadalya, Victoria S.; Kolomiets, Emilia I.; Aleschenkova, Zinaida M.; Karbanovich, Tatiana M. (Journal of the Belarusian State University. Ecology, 2020)
Under pilot-plant conditions on the excavated peat deposits in Smolevichsky (Minsk region) and Dokshitsky (Vitebsk region) areas results of relative research of influence mineral (Basacot Plus 6) and organic (Ekogum-complex, 5 and 10 %-s’ MaKloR) fertilizings on the biochemical composition of fruits American cranberry plants early-ripe Ben Lear and lateripening Stevens cultivars. It was shown that moving northward, cranberry fruits were depleted of 5−89 % ascorbic acid and free organic acids, soluble sugars, anthocyanins and leukoanthocyanines themselves with a decrease in the sugar acid index and the absence of changes in the content of pectin substances, against the background of activation by 7−74 % accumulation hydroxycinnamic acids, tannins, catechins and flavonols. In both research areas, the use of fertilizers contributed to the predominant enrichment of 5−41 % of the fruits of both cranberry varieties with anthocyanin pigments, soluble sugars, tannins and pectins and an increase in the sugar acid index against the background of their depletion by 7−46 % catechins, flavonols and hydroxycinnamic acids. It was shown that in the Smolevichi district, all tested agro-receptions contributed to an increase in the integral level of nutritional and vitamin value of cranberry fruits in the aggregate of 14 indicators 3−12 times in the Ben Lear cultivar and 4−8 times in the Stevens cultivar with the highest Basacot Plus 6 efficiency, along with the Ekohum complex was characterized by high efficiency for the early-ripening cultivar, and the microbial preparation MaKloR for the late-ripening variety, inferior in effectiveness to mineral fertilizer by 1.7−1.9 times. In the Dokshitsy district, with the introduction of Basacot Plus 6, a decrease in the integral level of the nutritional and vitamin value of late-ripening fruits was found to be 2.4 times lower than the control, while the use of organic fertilizers, on the contrary, ensured its increase by 3.5−8 times with the highest 10 % MaKloR performance.